2016
DOI: 10.1002/cphc.201600286
|View full text |Cite
|
Sign up to set email alerts
|

Noble‐Metal‐Free Materials for Surface‐Enhanced Raman Spectroscopy Detection

Abstract: Surface-enhanced Raman spectroscopy (SERS) is an attractive tool for the sensing of molecules in the fields of chemical and biochemical analysis as it enables the sensitive detection of molecular fingerprint information even at the single-molecule level. In addition to traditional coinage metals in SERS analysis, recent research on noble-metal-free materials has also yielded highly sensitive SERS activity. This Minireview presents the recent development of noble-metal-free materials as SERS substrates and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 91 publications
0
35
0
Order By: Relevance
“…Because of its unique layered structure, MoO 3 can theoretically exhibit a plasmonic effect upon the intercalation of small ions into its van der Waals gap . Here, hydrogen reduction by thermal treatment without metal catalysts is strategically designed to adjust the plasmonic peaks of MoO 3 so that it accompanies MoS 2 to achieve broadband absorption in the MoS 2 @MoO 3 hybrid nanostructures (see Figure b and the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its unique layered structure, MoO 3 can theoretically exhibit a plasmonic effect upon the intercalation of small ions into its van der Waals gap . Here, hydrogen reduction by thermal treatment without metal catalysts is strategically designed to adjust the plasmonic peaks of MoO 3 so that it accompanies MoS 2 to achieve broadband absorption in the MoS 2 @MoO 3 hybrid nanostructures (see Figure b and the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the high cost and scarcity of noble metals, integrating them with other cheap and sustainable nanomaterials is considered as one of the most effective strategies for modifying their properties and reducing their consumption . Alternatively, highly doped semiconductors represent another important class of plasmonic materials, which mainly involve transparent conducting oxides (TCO) and transition‐metal oxides/chalcogenides . In terms of the crustal abundance of elements and lower optical losses, highly doped semiconductors can outperform their noble‐metal counterparts in the photocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The effect was initially ascribed to the increased surface area of the roughened electrode, but in 1977 Albrecht and Creighton [6], and Jeanmaire and van Duyne [7], independently confirmed that the intense Raman signals actually reflected a true surface enhancement of the Raman scattering efficiency, as compared with the normal scattering crosssection of bulk pyridine. Currently, such enhancement can be directly observed in metal nanoparticles displaying plasmonic resonance, such as those of copper, silver and gold, and for this reason SERS has become a very important subject in nanotechnology and in medicine [2,[8][9][10][11][12][13][14][15][16] The SERS effect can also be observed in some semiconductors and graphene nanostructures involving surface plasmon resonance [17]; however, systematic studies are yet missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been reported that semiconductor nanostructures can exhibit good SERS performance, such as silicon nanowire, W 18 O 49 nanowire, ZnO nanocrystals, InAs/GaAs quantum dots, and Cu 2 O superstructure . It has been found that semiconductor‐based substrates possess excellent spectral reproducibility, high uniformity, and good anti‐interference ability, but their relatively low sensitivity still impedes their development for practical applications . The enhancement mechanism is based on the interfacial charge transfer (CT) between the semiconductor and molecules under the illumination.…”
mentioning
confidence: 99%